Networking and Collaboration as an Influencer on Sustainability of Public Borehole Water Projects in Kitui County-Kenya - musau, onesmus; Nyonje, Raphael Ondeko; Mulwa, Angeline (Advances in Social Sciences Research Journal, 2022)
The study focuses on networking and collaboration on sustainability of public boreholes water projects. The following was the objective; to assess the extent to which learning from networking and collaboration influences the sustainability of public borehole water projects in Kitui County-Kenya. The study tested the null hypothesis to establish whether the association among the study variable was significant. The target population was 366234 project beneficiaries, 396 chairpersons and 8 undertakers. A sample was drawn from this population using a formula adding to 383 project beneficiaries, 167 chairpersons and 8 undertakers. With R2=0.267, r=0.811, F(2,506) =30.41 at p=0.000, the hypothesis that there is no significant relationship between capacity building initiatives and sustainability of public borehole water projects in Kitui County-Kenya is therefore rejected. The findings from the study are expected to create a strong basis for enhancing future public borehole water project planning, designing, implementation, and management and also provided vital information for national government, county government, NGO’s, project managers, local communities and project implementers which was useful for initiating sustainable projects.